(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to provide references to young shorinji kempo coaches, athletes, and the general public in training the muscle strength of kempo athletes, namely, technique-based calisthenics physical training. This type of physical training is provided so that the training is not monotonous. This research is a research and development. The method in this study uses the research and development (R&D) method. This research was conducted in several steps, namely: identification of potential problems, information collection, product design, product creation, expert validation, product revision, trial, and final production. The subjects of this study were kempo athletes of beginner, junior, and senior ages. The data collection technique used in this study was an instrument in the form of an assessment sheet. The data analysis technique of this study was descriptive qualitative and descriptive quantitative. The results of this study are that the development of the Calisthenics training model using media from the media validation analysis is qualified as valid.